2018
DOI: 10.3390/molecules23092119
|View full text |Cite
|
Sign up to set email alerts
|

Linking Aromatic Hydroxy Metabolic Functionalization of Drug Molecules to Structure and Pharmacologic Activity

Abstract: Drug functionalization through the formation of hydrophilic groups is the norm in the phase I metabolism of drugs for the modification of drug action. The reactions involved are mainly oxidative, catalyzed mostly by cytochrome P450 (CYP) isoenzymes. The benzene ring, whether phenyl or fused with other rings, is the most common hydrophobic pharmacophoric moiety in drug molecules. On the other hand, the alkoxy group (mainly methoxy) bonded to the benzene ring assumes an important and sometimes essential pharmaco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 71 publications
0
16
0
Order By: Relevance
“…The chemical classification of NSAIDS is given in the first part of this review series [12]. The two NSAIDS considered in this section, ibuprofen and tolmetin are of the arylalkanoic acid class.…”
Section: Nsaidsmentioning
confidence: 99%
See 3 more Smart Citations
“…The chemical classification of NSAIDS is given in the first part of this review series [12]. The two NSAIDS considered in this section, ibuprofen and tolmetin are of the arylalkanoic acid class.…”
Section: Nsaidsmentioning
confidence: 99%
“…Loss of pharmacologic activity has been observed for ibuprofen upon metabolic hydroxylation of the isobutyl group at C1, C2, and C3 ( Figure 3). In analogy with the O-demethylation of the methoxy-group-containing NSAIDS discussed in the first part of this review series [12], both pharmacodynamic and pharmacokinetic effects may account for the ibuprofen isobutyl-hydroxy metabolites' loss of pharmacologic activity. The SAR of ibuprofen dictates that the branched isobutyl moiety is essential for optimum COX-inhibitory effect; in this context, n-butyl substitution has led to significant loss of activity [101].…”
Section: Nsaidsmentioning
confidence: 99%
See 2 more Smart Citations
“…While no further in vitro or in vivo studies have been reported for compound A however we anticipated that the presence of OMe group (activated by the +M effect of pyrazole ring) exposed outside at the para ‐position could be a metabolic burden of these molecules. It is known that drugs or bioactive agents containing a methoxy group generally undergo metabolism involving the demethylation of the methoxy group in the presence of cytochrome P450 (CYP) isoenzymes [10,11] . To avoid this issue we designed an alternative pyrazole based framework B (Figure 1) in which the methoxy phenyl moiety was moved to the nitrogen atom with the shifting of OMe group from para ‐ to the ortho ‐position.…”
Section: Introductionmentioning
confidence: 99%